Alternative Ecological Risk Assessment : an Innovative Approach to Understanding Ecological Assessments for Contaminated Sites. - Tannenbaum, Lawrence (Wiley-Blackwell, 2013)
In Alternative Ecological Risk Assessment the author, Lawrence V. Tannenbaum, provides a critical review of current practices in the ecological risk assessment field and proposes alternatives that are supported by established science and keen observation. It is hoped that this approach will pave the way to a greater understanding of what appropriate and useful ecological assessment for contaminated sites should entail. He demonstrates that in most cases current practices do not provide for an assessment of ecological risk, and moreover, that endeavoring to assess ecological ri.